Investigating dissolved air flotation performance with cyanobacterial cells and filaments - Teixeira, M. R. (2010)
Dissolved air flotation (DAF) performance with two different naturally occurring cyanobacterial morphologies was investigated with respect to the biomass removal efficiency, the toxin release to water and the coagulant demand by different water background natural organic matter (NOM). Coagulation (C)/Flocculation (F)/DAF bench-scale experiments (2 min coagulation at 380 s 1 with polyaluminium chloride (0.5e4 mg/L Al2O3, the dose depending on the water NOM content); 8 min flocculation at 70 s 1; 8 min DAF with 5 bar relative pressure and 8% pressurised recycle) were performed with single cells of Microcystis aeruginosa and Planktothrix rubescens filaments spiked in synthetic waters with different NOM contents (hydrophobic vs. hydrophilic NOM; moderate (2e3 mgC/L) vs. moderate-high concentration (ca. 6 mgC/L)). For both morphologies, the results show no apparent cyanobacterial damage (since the water quality did not degrade in dissolved microcystins and the removal of intracellular microcystins matched the removal of chlorophyll a) and high biomass removal efficiencies (93e99% for cells and 92e98% for filaments) provided optimal coagulant dose for chlorophyll a removal was ensured. Charge neutralisation by the polyaluminium chloride was the main coagulation mechanism of the M. aeruginosa cells and most likely also of the P. rubescens filaments. The specific coagulant demand was severely affected by NOM hydrophobicity, hydrophobic NOM (with a specific UV254nm absorbance, SUVA, above 4 L/(m mgC)) requiring ca. the triple of hydrophilic NOM (SUVA below 3 L/(m mgC)), i.e. 0.7 vs. 0.2e0.3 mg Al2O3/mg DOC.